Early Predictors of Mortality in Children with Severe Dengue Fever: A Prospective Study. Issue 9 (27th July 2021) - Sachdev, Anil; Pathak, Divyank; Gupta, Neeraj; Simalti, Ashish; Gupta, Dhiren; Gupta, Suresh; Chugh, Parul
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: The aim of the study was to identify early predictors of mortality in children with severe dengue fever admitted to pediatric intensive care unit (PICU). Materials and Methods: All consecutive children with laboratory-confirmed severe dengue fever were enrolled in this prospective observational study. Besides demographic data, disease severity and organ dysfunction scores, laboratory investigations and interventions are done in PICU were recorded and analyzed. Results: During the study period of 42 months, 172 patients with dengue fever were admitted to PICU. A total of 78 (45.3%) patients with severe dengue fever were included and analyzed. There were 20 (25.6%) deaths. There were significant differences in disease severity and organ dysfunction scores, transaminases, blood lactate level and serum creatinine between survivors and nonsurvivors. A significantly higher number of nonsurvivors required interventions in first 24 hours of admission. Platelet counts ( P value 0.22) and hematocrit ( P value 0.47) were not statistically different in 2 groups. There was a significantly high vasopressor—inotrope score (VIS) (<0.001) and positive fluid balance >10% (0.002) in nonsurvivors. Multivariate stepwise logistic regression analysis identified serum glutamic pyruvic transaminases (≥ 284 IU/L; odds ratio [OR] 1.002, 95% confidence interval [CI]: 1.001–1.003), blood lactate level (≥2.73 mmol/L; OR 2.08, 95% CI: 1.354–3.202), Pediatric Risk of Mortality score at 12 hours (≥14.5; OR 1.35, 95% CI: 1.077–1.693), VIS (≥22.5, OR 1.129, 95% CI: 1.059–1.204) and positive fluid balance >10% (OR 22.937, 95% CI: 2.393–219.84) at 24 hours of admission as independent predictors of mortality. Conclusion: Disease severity, hyperlactatemia at admission, need for multiple vasoactive drugs and positive fluid balance are predictors of mortality in severe dengue infection in children admitted to PICU.